Toksik Liderliğin Çalışanların Tükenmişlik Düzeylerine Etkisi - Uzunbacak, Hasan Hüseyin; Yıldız, Aslıhan; Uzun, Sercan (Muş Alparslan Üniversitesi, 2019)
Leadershipis crucial for realizing the objectives of businesses. The behaviors of theleaders are influential on the employees. One of the most important of theseeffects is on the burnout levels of employees. In the research conducted, positive types of leadership are generally considered and there is a strongrelationship between leadership style and burnout level of employees. In thisresearch, the relationship between Toxic Leadership and Burnout is considered.241 blue-collar employees working in three textile firms operating in theprovince of Denizli were included in the survey The collected data were testedaccording to the structural equation model with SPSS and Lisrel programs. Accordingto this study, there is a positive and significant relationship between badacting leader and autocratic leader sub-dimensions and burnout perceptions thattoxic leadership is directly related to behavior style. According to this, burnout levels are also rising if they perceive to a high level that employees'leaders behave badly and autocratically. There was no correlation between othertoxic leadership sub-dimensions and employees’ burnout.

Liderlik, işletmelerin amaçlarını gerçekleştirmek için oldukça önemlidir. Liderlerinsergiledikleri davranışlar çalışanlar üzerinde etkili olmaktadır. Bu etkilerdenen önemlilerinden birisi de çalışanların tükenmişlik düzeyleri üzerindeolmaktadır. Yapılan araştırmalarda, genellikle liderliğin olumlu türleri elealınmış ve liderlik tarzıyla çalışanların tükenmişlik düzeyi arasında güçlüilişkilerin olduğu belirtilmektedir. Bu araştırma da ise, olumsuz etkileresebep olan Toksik Liderlik ile Tükenmişlik arasındaki ilişki ele alınmaktadır.Araştırmaya Denizli ilinde faaliyet gösteren üç tekstil firmasında çalışan 241mavi yakalı çalışan dâhil edilmiştir. Toplanan veriler, SPSS ve Lisrel paketprogramlarıyla yapısal eşitlik modeline göre test edilmiştir. Toksik liderliğindoğrudan davranış tarzıyla ilgili olduğu değerlendirilen kötü davranan lider veotokratik liderlik boyutu ile tükenmişlik algıları arasında ilişki bulunmuştur.Buna göre, çalışanların liderlerinin kötü davrandığını ve otokratik tarzdayönetim sergilediğini yüksek düzeyde algılamaları durumunda tükenmişlikdüzeyleri de yükselmektedir. Kişilik özelliği olarak değerlendirilebilecekdiğer toksik liderlik boyutları ile çalışanların tükenmişlik düzeyleri arasındailişki bulunamamıştır.
The Effect of Toxic Leadership on the Burnout Levels of Employee
anemon
Keywords: Leadership; Toxic leadership; Burnout; Liderlik; Toksik liderlik; Tükenmişlik